A common variant at the TERT-CLPTM1L locus is associated with estrogen receptor-negative breast cancer - Haiman, Christopher A.; Canzian, Federico; Chang-Claude, Jenny; Hamann, Ute; Kaaks, Rudolf; Sinn, Peter (Nature genetics, 2011)
Christopher Haiman and colleagues report a genome-wide association study for estrogen receptor (ER)-negative breast cancer in women of African and European ancestry. They identify a variant at the TERT-CLPTM1L locus on 5p15 as associated with ER-negative and triple-negative breast cancer. This locus also harbors multiple variants associated with a range of other cancers.
Gesehen am 29.07.2022